The Urgency of Strategic Plan Management in Improving Madrasah Quality: Urgensi Manajemen Rencana Strategis dalam Meningkatkan Kualitas Madrasah - Istikomah, Istikomah; Romadlon , Dzulfikar Akbar; Nadlif , Ainun (Universitas Muhammadiyah Sidoarjo, 2023)
Madrasah in Indonesia are educational institutions whose curriculum contains Islamic lessons, which are often managed without proper planning. In this paper, the author will conduct a conceptual study based on existing literature regarding preparing strategic plans for improving management in madrasas. The conclusion of this study shows that strategic planning is essential in determining the direction of madrasah development in the future. Before compiling the madrasah strategic planning document, define the vision and mission to be achieved by all stakeholders. Then the madrasa conducts a SWOT analysis to determine its strengths and weaknesses and performs an environmental analysis to determine the weaknesses and strengths of the institution for the successful achievement of its mission and goals. After all stakeholders in the madrasa know the institution's condition, it is necessary to set targets that need to be evaluated annually. Highlights: Strategic Planning: Strategic planning is crucial for determining the future development direction of madrasahs, ensuring effective management and achievement of goals. SWOT Analysis: Conducting a SWOT analysis helps identify the strengths, weaknesses, opportunities, and threats of the madrasah, guiding decision-making and improvement efforts. Stakeholder Involvement: Involving all stakeholders in defining the vision, mission, and strategic goals fosters a shared sense of ownership and commitment to the madrasah's success. Keywords: Madrasah, Strategic Planning, SWOT Analysis, Stakeholders, Targets